RESPON SIFAT FISIKA INCEPTISOL TERHADAP PEMBERIAN BLOTONG DAN PUPUK KANDANG SAPI - Amri Amanah (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2021)
Organic matter plays a role in forming structures, improving aggregate stability and increasing soil water availability. This study aims to determine the response of the soil to the application of two types of organic matter by observing the physical properties of the soil such as bulk density, aggregate stability, meso pores, micro pores, and available water. The research was conducted at Agricultural Training, Research and Development Station Gadjah Mada University Yogyakarta. The strip-split-plot design in an Randomized Complete Block layout with three factors was used to this experimental. The first factor was two types of organic matters, namely cow manure and press mud. The second factor was dose of organic matter, namely control, 1 t.ha‑1, 2 t.ha-1, and 3 t.ha‑1. The third factor was two inbreed lines of paddy which adaptive to dry-land condition, namely line 11 and line 12. The results showed that organic matter had a significant effect on aggregate stability and meso pores, but did not significantly influence bulk density, micro pores, and available water. The aggregate stability was higher and meso pores was smaller while bulk density and available water was lower with press mud. Keywords : cow manure, filter mud, organic matter, paddy, soil physical properties